2016
DOI: 10.1186/s12889-016-3343-z
|View full text |Cite
|
Sign up to set email alerts
|

Service evaluation of an educational intervention to improve sexual health services in primary care implemented using a step-wedge design: analysis of chlamydia testing and diagnosis rate changes

Abstract: BackgroundProviding sexual health services in primary care is an essential step towards universal provision. However they are not offered consistently. We conducted a national pilot of an educational intervention to improve staff’s skills and confidence to increase chlamydia testing rates and provide condoms with contraceptive information plus HIV testing according to national guidelines, known as 3Cs&HIV. The effectiveness of the pilot on chlamydia testing and diagnosis rates in general practice was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Data from the quantitative analysis showed that 58% (268/460) of practices that agreed to participate in the intervention received at least one educational workshop [19]. When discussing reasons for their colleagues non-attendance at the educational workshops, participants reported reasons, such as: lack of time (especially GPs); staff feeling that it is not their field, role, or area of expertise (especially male, older GPs); and the perception that chlamydia tests are offered in contraception consultations, which are generally for female patients, who prefer to see female staff.

“We didn’t complete it… only did the chlamydia and it’s not because she didn’t try, she kept trying to get in, but we had a massive, massive staff change round and then we’ve had a lot of sickness so I couldn’t, I just cannot get the meetings together for the rest of them.” (YNYER121- nurse)

“you’re going to find that female staff will go… it’s also in your area of speciality and it’s going to be interesting whereas, yeah, someone who’s just not got that in their kind of bag is not, unless it’s a learning need for them, they’re probably not going to rush to be there… are going to miss training” (DCR120- GP)

“[male GP talking about patient’s preference]…see the female doctors for, for consultations… I think it’s less of an issue less of something I’ve had to deal with than some of my colleagues but that of course puts me at risk of being less good at it” (NSKT124- GP)

…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from the quantitative analysis showed that 58% (268/460) of practices that agreed to participate in the intervention received at least one educational workshop [19]. When discussing reasons for their colleagues non-attendance at the educational workshops, participants reported reasons, such as: lack of time (especially GPs); staff feeling that it is not their field, role, or area of expertise (especially male, older GPs); and the perception that chlamydia tests are offered in contraception consultations, which are generally for female patients, who prefer to see female staff.

“We didn’t complete it… only did the chlamydia and it’s not because she didn’t try, she kept trying to get in, but we had a massive, massive staff change round and then we’ve had a lot of sickness so I couldn’t, I just cannot get the meetings together for the rest of them.” (YNYER121- nurse)

“you’re going to find that female staff will go… it’s also in your area of speciality and it’s going to be interesting whereas, yeah, someone who’s just not got that in their kind of bag is not, unless it’s a learning need for them, they’re probably not going to rush to be there… are going to miss training” (DCR120- GP)

“[male GP talking about patient’s preference]…see the female doctors for, for consultations… I think it’s less of an issue less of something I’ve had to deal with than some of my colleagues but that of course puts me at risk of being less good at it” (NSKT124- GP)

…”
Section: Resultsmentioning
confidence: 99%
“…Practices that had participated in the 3Cs and HIV intervention were stratified by chlamydia screening rate per 100 registered 15–24 year old patients, from January 2013 until September 2014 [19]. Practices were then contacted in a random order from this list via the practice managers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations